Analysis of T cell subsets in Graves' disease: alterations associated with carbimazole. Issue 6416 (18th February 1984) - Ludgate, M E; McGregor, A M; Weetman, A P; Ratanachaiyavong, S; Lazarus, J H; Hall, R; Middleton, G W
Abstract : Conflicting data on subpopulations of peripheral blood lymphocytes in patients with autoimmune disease largely reflect variations in methods of study. An investigation was therefore conducted aimed at avoiding this difficulty. Serial samples of peripheral blood mononuclear cells from 42 patients with hyperthyroid Graves' disease were collected at monthly intervals before, during, and for 12 months after a six month course of carbimazole. Samples were stored in liquid nitrogen until completion of the study, when they were thawed and all samples from each patient analysed within the same assay using mouse monoclonal antibodies to human cell subsets and a fluorescence activated cell sorter. Proportions of cytotoxic/suppressor (OKT8) positive cells before treatment (mean 17.4 (SEM 0.8)%) were significantly lower (p less than 0.001) than those in normal controls (29.8 (1.9)%; n = 10) and returned to normal by the end of treatment. In contrast, the proportions of activated T cells (OKIa-OKM1) were significantly raised before treatment as compared with normal (14.4 (0.6)% versus 4.6 (0.8)%; p less than 0.001) and fell to normal by the end of treatment. Proportions of OKT3 and OKT4 positive T cells remained unchanged throughout treatment and in the succeeding 12 months. In patients who relapsed after treatment there was a rise in the proportion of activated T cells and a fall in OKT8 positive T cells, which returned towards normal with retreatment. The explanation for the alterations in numbers of circulating T cells remains to be determined but they may provide a means for predicting more accurately the outcome of Graves' disease after treatment with carbimazole.